Asymmetric synthesis of (+)-stagonolide C and (-)-aspinolide A via organocatalysis - Shelke, Anil M.; Rawat, Varun; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2012)
A new enantioselective synthesis of two important fungal metabolites, (+)-stagonolide C and (-)-aspinolide A, has been described from readily available raw materials. Praline catalyzed asymmetric alpha-aminooxylation and Jorgensen's epoxidation of aldehydes are the key reactions employed in the introduction of chirality. The formation of the 10-membered lactone core structure was finally accomplished via Steglich esterification and ring closing metathesis reactions. (C) 2012 Elsevier Ltd. All rights reserved.